ANALYSIS OF SUPPLY CHAIN MANAGEMENT OF AND PARTNERSHIP PATTERNS IN VEGETABLE ONLINE COMPANY: CASE STUDY AT BEJANA.ID - Vania Azalia Anabel; Zainal Abidin; Novi Rosanti (Lampung University, 2023)
This study aims to analyze supply chain management of vegetable products, identify supply chain performance based on the estimation of average time and partnership patterns at Bejana.id, Bandar Lampung. The case study method was used to determine the location purposively. Data were collected using questionnaires in December 2022. The sample used purposive sampling, including one person from Bejana.id, six merchant partners, and nine farmer partners. The data analysis method applied for supply chain management and partnership pattern is qualitative, and supply chain management performance is Supply Chain Operation References (SCOR). The results indicated that (1) the Bejana.id supply chain includes farmer and merchant partners, Bejana.id, and B2B (Business to Business) & B2C (Business to Consumers). The flow of products, information, and money are efficient and have not found severe issues, (2) supply chain performance at the supplier partner level is an advantage in standardized products (SP) and parity in perfect order fulfilment (POF), and for the Bejana.id level get the advantage in standardized products (SP), (3) the partnership pattern between Bejana.id and farmer partners is the common trade pattern, and between Bejana.id and merchant partners is the agency pattern. Keywords: e-commerce, partnership, SCOR, supply chain, vegetables